Geography Learning Models in Improving Spatial Thinking Skills: A Literature Review - Dewi, Ratri Purnama; Saidi, Ridwan; Somantri, Lili; Maryani, Enok (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2025)
Spatial thinking skills are essential in everyday life. These skills can be improved through geography learning. Various studies on efforts to improve spatial thinking skills through geography education have been conducted in Indonesia; however, none have specifically examined the various models, teaching materials, and learning outcomes. Through a comprehensive review of previous findings, this study was conducted to fill this gap. The results of this study can be helpful for teachers and researchers in further developing geography education. This study employs a qualitative research design, specifically a document study or literature review. Publish or Perish software is used in the process of exploring or conducting literature searches. Through the initial search process, a total of 61 documents were obtained. These documents were then reviewed individually, resulting in a total of 16 documents that met the inclusion criteria. The results of the study showed that the most widely applied geography learning model was Project-Based Learning, followed by Discovery Learning and EarthComm. The teaching materials used are Disaster and Disaster Management, Basics of Mapping, Remote Sensing, and Geographic Information Systems (GIS), Atmosphere, Hydrosphere, Lithosphere Dynamics and Its Impact on Life, and Potential of Indonesian Marine Waters. Through the application of the learning model, various improvements were obtained in several indicators of spatial skills. The Project-Based Learning model is the most successful approach in improving various indicators of spatial thinking skills, including Analogy, Aura, Pattern, Association, Form, and Analysis.